Ifosfamide, Carboplatin, and Etoposide (ICE) in Combination with Regional Hyperthermia as Salvage Therapy in Patients with Locally Advanced Nonmetastatic and Metastatic Soft-Tissue Sarcoma. (1st March 2020) - Bücklein, Veit; Limmroth, Christina; Kampmann, Eric; Schuebbe, Gesa; Issels, Rolf; Roeder, Falk; Angele, Martin; Dürr, Hans Roland; Knösel, Thomas; Abdel-Rahman, Sultan; Di Gioia, Dorit; Lindner, Lars H.
Abstract : Patients with localized relapse of soft-tissue sarcoma (STS) after anthracycline-based chemotherapy have a dismal prognosis, particularly when surgery is not possible. To facilitate resection and improve long-term tumor control, we applied an intensified perioperative treatment consisting of ICE (ifosfamide 6 g/m 2, carboplatin 400 mg/m 2, and etoposide 600 mg/m 2 ) in combination with regional hyperthermia (RHT) to maximize local control. Here, we retrospectively evaluate the safety and efficacy of this strategy. Patients aged ≥18 years with locally advanced high-risk STS, either with or without metastasis, treated with ICE + RHT after the failure of first-line anthracycline-based chemotherapy were included in this analysis. Radiographic response, toxicity, progression-free survival (PFS), and overall survival (OS) were assessed. Between 1996 and 2018, 213 sarcoma patients received ICE at our centre. Of these, 110 patients met the selection criteria (progressive disease, suitable high-grade STS histology, anthracycline pretreatment, RHT treatment) for this analysis. Fifty-four patients had locally advanced disease without metastases (LA-STS), and 56 patients had additional metastatic disease (M-STS). Disease control was achieved in 59% of LA-STS patients and in 47% of M-STS patients. For LA-STS, 21% of the patients achieved radiographic response, facilitating resection in 4 patients (7%), compared with 11% of the M-STS patients, facilitating resection in 5 patients (9%). PFS was significantly longer in LA-STS than in M-STS (10 vs. 4 months, p < 0.0001 ). Median OS was 26 months in LA-STS and 12 months in M-STS. Disease control was the only independent prognostic factor for improved OS in multivariate analysis. Toxicity was high with neutropenic fever occurring in 25% of the patients and three therapy-related deaths (3%). ICE + RHT demonstrated activity in high-risk STS and facilitated resection in selected patients after anthracycline failure. Disease control was associated with improved OS. Based on the observed toxicities, the dose should be reduced to 75%.